The Navigating Cultural Sensitivity in Kamila Shamsie's Home Fire - Ansar, Mohammed; Saeed, Omera (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2025)
This study explores the depiction of intercultural sensitivity in Kamila Shamsie's novel Home Fire (2017), focusing on the complexities of cultural identity, family dynamics, love, belonging, and power relations. It examines the novel’s characters and their relationships to demonstrate how Shamsie addresses the tension between cultural heritage and national identity. The study emphasizes the importance of empathy, compassion, and cultural competence in fostering meaningful connections across cultural divides. The research adopts a qualitative methodology, approaching the text through a hermeneutic lens, with Bennett's Developmental Model of Intercultural Sensitivity 1986 serving as a framework to examine the underlying cultural dynamics.